Je suis ça : voices that clamor from the mountain - Kiburytė, Renata (Escritura e Imagen, 2019)
Since the publication of the expurgated version of the “Diary” of Nijinsky in 1936, it has been considered a document of self-analysis that documents the development of a mental crisis. Joan Acocella, the editor of the first unexpurgated version of the diary published in English in 1999 reflects on the beauty and “nobility” of the text that had been rewritten by Romola Nijinsky and was the only version known until then, almost preferring it over the original. For her the main value of publishing Nijinsky’s text as it had been written by him is documental. In this article, with the aid of various texts by Jean-Luc Nancy, we will try to offer a different reading and to look for a different meaning (or rather sense) that this almost illegible text could have. We will look at several drawings made by Nijinsky and we will evoke the experience of dance in order to open up the sounds and the senses of the writing. It could be that what we will find is an existence “in crisis”, that is an existence that ex–sists, that opens, that se détache. It could be that what we will find is the creation of a world.